2006
DOI: 10.1104/pp.106.090324
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Evolution of CYCLOIDEA-Like TCP Genes in Relation to Flower Development in Papaveraceae

Abstract: Monosymmetry evolved several times independently during flower evolution. In snapdragon (Antirrhinum majus), a key gene for monosymmetry is CYCLOIDEA (CYC), which belongs to the class II TCP gene family encoding transcriptional activators. We address the questions of the evolutionary history of this gene family and of possible recruitment of genes homologous to CYC in floral development and symmetry in the Papaveraceae. Two to three members of the class II TCP family were found in each species analyzed, two of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 64 publications
3
83
0
1
Order By: Relevance
“…A recent study in legumes, distantly related to A. majus, shows that a CYC homologue LjCYC2 also establishes adaxial identity in the legume flowers (Feng et al 2006). In the basal eudicot family Papaveraceae sensu lato, the duplication and diversification of CYC-like TCP genes are accompanied by their divergence in expression patterns, in which one type of them may play a role in flower symmetry (Kölsch and Gleissberg 2006;Damerval et al 2007). These facts indicate that the basic function of CYC and its homologues seems to be conserved in eudicots, i.e., controlling the development of floral asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study in legumes, distantly related to A. majus, shows that a CYC homologue LjCYC2 also establishes adaxial identity in the legume flowers (Feng et al 2006). In the basal eudicot family Papaveraceae sensu lato, the duplication and diversification of CYC-like TCP genes are accompanied by their divergence in expression patterns, in which one type of them may play a role in flower symmetry (Kölsch and Gleissberg 2006;Damerval et al 2007). These facts indicate that the basic function of CYC and its homologues seems to be conserved in eudicots, i.e., controlling the development of floral asymmetry.…”
Section: Introductionmentioning
confidence: 99%
“…The plane of bilateral symmetry in Fumariodeae flowers is transverse (figure 4), although partial resupination ultimately brings the transverse plane into dorsoventral orientation. In Capnoides, expression of two CYC-lineage paralogues [40,41] is asymmetric, with slightly stronger expression at the base of the outer petal that forms a nectary [76].…”
Section: (B) Rosidsmentioning
confidence: 99%
“…And again, we find evidence supporting a role for CYC-like genes in the development of bilaterally symmetrical flowers from early diverging eudicot and monocot lineages. Bilaterally symmetrical flowers of Capnoides in the Fumariodeae lineage of Papaveraceae (Ranunculales) are derived from disymmetric flowers [40,41]. The plane of bilateral symmetry in Fumariodeae flowers is transverse (figure 4), although partial resupination ultimately brings the transverse plane into dorsoventral orientation.…”
Section: (B) Rosidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, great progress has been made in functional characterization of the class II TCPs in Arabidopsis. These transcription factors play important roles in leaf, flower, shoot morphogenesis, and hormone biosynthesis (Damerval et al, 2007;Koyama et al, 2007;Schommer et al, 2008;Nag et al, 2009;Guo et al, 2010). The cellular functions of class I TCPs are less well explored, but several previous studies indicated that they are involved in a number of cellular or developmental processes.…”
mentioning
confidence: 99%